(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The current research aims to identify the level of ethical thinking skills and the statistically significant differences in ethical thinking skills according to gender and major variables. The research sample consisted of 300 male and female fifth-grade students from Al-Alam district schools, selected using a stratified random sampling method. The researcher constructed a scale of ethical thinking skills, which in its final form consisted of 36 items after calculating the discriminatory power and extracting the scale’s psychometric properties. Using the SPSS statistical program, the results showed the following: The research sample enjoyed a good level of ... -There was a statistically significant difference between students majoring in science and students majoring in the humanities, in favor of science . -There were statistically significant differences between males and females, in favor of males . In light of the results of the current research, a number of recommendations and proposals were formulated .